Pengaruh Citra Merek dan Potongan Harga terhadap Keputusan Pembelian Melalui OFD Gofood: Studi Pada Mahasiswa Manajemen UPN “Veteran” Jawa Timur - Lestari, Windi Putri; Soebiantoro, Ugy; Amriel, Egan Evanzha Yudha (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
In the era of globalization, everything, including information technology and communication, become easier. Digitalization has penetrated various aspects of society’s life, including culinary businesses, resulting in the emergence of various smartphone applications offering Online Food Deliver (OFD) services, one of which is Gofood. The purpose of this research is to determine the influence of brand image and price discounts on purchasing decisions through Online Food Delivery Gofood among management students of Universitas Pembangunan Nasional “Veteran” Jawa Timur. This study uses the Partial Least Square (PLS) method with a sample of 96 respondents. The results show that brand image and price discounts have a positive and significant effect on purchasing decisions. Keywords: Brand Image; Online Food Delivery; Price Discounts; Purchase Decisions